Winter fire - Lowell, Elizabeth, 1944- (Avon Books, 1996)
For two years Sarah Kennedy, a mail-order bride experiences painful sex at the hands of her husband, a brutal farmer. The experience leaves her hating sex, even after he dies. But one day there stumbles into her farmhouse lawman Case Maxwell and as she heals his wounds desire revives.